Integration of Indonesian Coffee Markets with World Coffee Markets - Haposan Orlando Napitupulu; Ana Arifatus Sa'diyah; Farah Mutiara (Journal of Agricultural Socio-Economics (JASE), 2021)
This study aims to analyze the integration of the Arabica and Robusta coffee markets in Indonesia with world coffee prices. The study uses secondary data in the form of annual time series data during the period 1985 - 2015. The study uses the VECM analysis method. This method explains the relationship of long-term dynamic equilibrium and short-term equilibrium in a system of equations. The analysis shows that Indonesian and world Arabica coffee is not integrated in the long term or the short term. In Robusta coffee VECM estimation analysis shows that there is a significant value at the 10% level in a long-term relationship with a value of 0.08579, which means that there is a short-term relationship between world Robusta coffee prices and domestic Robusta coffee prices in the previous year, but no relationship in the long run.